Correction to: The Potato of the Future: Opportunities and Challenges in Sustainable Agri-Food Systems - Devaux, A.; Goffart, J.; Kromann, P.; Andrade-Piedra, J.L.; Polar, Vivian; Hareau, Guy (Springer, 2022)
The original version of the article unfortunately contained an error. In line 4 of the abstract, it appears that by mistake a few words were added in the middle of another sentence - "especially the case in Africa where". The correct sentence is: Food security has four dimensions: food availability, food access, food use and quality, and food stability.